Tremor in motor neuron disease may be central rather than peripheral in origin - Latorre, Anna; Balint, Bettina (European journal of neurology, 2019)
Background and purpose Motor neuron disease (MND) refers to a spectrum of degenerative diseases affecting motor neurons. Recent clinical and post-mortem observations have revealed considerable variability in the phenotype. Rhythmic involuntary oscillations of the hands during action, resembling tremor, can occur in MND, but their pathophysiology has not yet been investigated. Methods A total of 120 consecutive patients with MND were screened for tremor. Twelve patients with action tremor and no other movement disorders were found. Ten took part in the study. Tremor was recorded bilaterally using surface electromyography (EMG) and triaxial accelerometer, with and without a variable weight load. Power spectra of rectified EMG and accelerometric signal were calculated. To investigate a possible cerebellar involvement, eyeblink classic conditioning was performed in five patients. Results Action tremor was present in about 10% of our population. All patients showed distal postural tremor of low amplitude and constant frequency, bilateral with a small degree of asymmetry. Two also showed simple kinetic tremor. A peak at the EMG and accelerometric recordings ranging from 4 to 12 Hz was found in all patients. Loading did not change peak frequency in either the electromyographic or accelerometric power spectra. Compared with healthy volunteers, patients had a smaller number of conditioned responses during eyeblink classic conditioning. Conclusions Our data suggest that patients with MND can present with action tremor of a central origin, possibly due to a cerebellar dysfunction. This evidence supports the novel idea of MND as a multisystem neurodegenerative disease and that action tremor can be part of this condition.
First published: 28 June 2018
Gesehen am 06.09.2019